Studi Kritis Bahan Ajar Al-qur’an Hadis Materi Perilaku Jujur dalam Bermuamalah Kelas XI MTs Hidayatul Falah Sukabumi - Vera Siti Magfiroh; Siti Qomariyah; Salsabila Salsabila; Ridwan Hermawan; E. Komarudin (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Instilling the value of honesty in muamalah (social and economic interactions) is an essential component of Islamic character education, particularly in shaping students' moral foundation. This study critically examines the teaching materials used in the subject of Qur’an and Hadith for Grade IX students at MTs Hidayatul Falah, focusing on the theme “Honest Behavior in Muamalah.” The research employed a qualitative approach with a descriptive analysis method. Data were obtained through the examination of teaching documents, classroom observations, and interviews with educators. The findings reveal that the materials used address three key learning domains: cognitive (knowledge-based), affective (attitudinal), and psychomotor (behavioral). However, the content tends to overemphasize the cognitive domain, often presenting honesty and the importance of keeping promises merely as theoretical constructs without sufficient contextualization. While the materials are based on authentic Qur’anic verses and hadiths, they fall short in connecting those teachings to real-life scenarios that are relatable to students’ daily experiences, particularly in the context of modern adolescent challenges such as academic integrity, social media behavior, and financial transactions. Additionally, the dominant instructional method is still conventional, with limited use of interactive and student-centered strategies. As a result, students are less likely to internalize and practice these moral values meaningfully. The study underscores the need to develop more dynamic and contextualized teaching resources that incorporate active learning techniques, such as case studies, role-playing, and reflective discussions. These methods can enhance student engagement, critical thinking, and self-reflection, thereby fostering a deeper understanding and genuine application of honesty in everyday muamalah. Strengthening the relevance and delivery of religious character education is vital for preparing students to become ethically responsible individuals in both personal and social contexts.